2021
DOI: 10.3389/fmicb.2020.574110
|View full text |Cite
|
Sign up to set email alerts
|

Phytophthora Root Rot Modifies the Composition of the Avocado Rhizosphere Microbiome and Increases the Abundance of Opportunistic Fungal Pathogens

Abstract: The structure and function of rhizosphere microbial communities are affected by the plant health status. In this study, we investigated the effect of root rot on the avocado rhizosphere microbiome, using 16S rDNA and ITS sequencing. Furthermore, we isolated potential fungal pathogens associated with root rot symptoms and assessed their pathogenic activity on avocado. We found that root rot did not affect species richness, diversity or community structure, but induced changes in the relative abundance of severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 84 publications
3
22
0
Order By: Relevance
“…For example, the abiotic environment has been reported to strongly drive the composition of the plant microbiome, including soil [ 1 , 2 , 3 ], atmosphere [ 4 ], geography [ 5 , 6 ], and many others. In addition, the plant microbiome is under the influence of many biotic factors, some of them exogenous like herbivory [ 1 , 7 ] or plant diseases [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], some others are instead driven by the plant itself. Indeed, previous studies reported variation in the structure of plant microbiomes according to compartment (e.g., root, leaf, fruit, flower) [ 18 ], but also within the same compartment, for example between different parts of flowers and fruits, or between internal and external tissues [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the abiotic environment has been reported to strongly drive the composition of the plant microbiome, including soil [ 1 , 2 , 3 ], atmosphere [ 4 ], geography [ 5 , 6 ], and many others. In addition, the plant microbiome is under the influence of many biotic factors, some of them exogenous like herbivory [ 1 , 7 ] or plant diseases [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ], some others are instead driven by the plant itself. Indeed, previous studies reported variation in the structure of plant microbiomes according to compartment (e.g., root, leaf, fruit, flower) [ 18 ], but also within the same compartment, for example between different parts of flowers and fruits, or between internal and external tissues [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our study highlighted discrepancies in rhizosphere resistances of mingled afforestation to maintain sustainability of forest health, and provided new insights into the mechanism of rhizosphere defense of trees to bio-stress (Massart et al 2015;Solís-García et al 2021).…”
Section: Discussionmentioning
confidence: 86%
“…Endophytic microbes and those found in the rhizosphere are generally known to be beneficial to plants, promoting their growth through the supply of phytohormones, critical nutrients and/or the inhibition of pathogens -either directly or indirectly -by activating the hosts' induced systemic resistance mechanisms (Suryadi et al, 2019). 16 s rDNA profiling and metagenomic assessment of healthy and P. cinnamomi infected avocado tree soil showed a marked difference in the microbial rhizosphere community (Yang et al, 2001;Shu et al, 2019;Solís-García et al, 2021). Pseudomonas genus and Serratia sp.…”
Section: Discussionmentioning
confidence: 99%